(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
The study aims to evaluate the effects of creep feed and commercial concentrates on the growth performance of pre-weaning Dorper lambs in accelerated lambing production. The Dorper lambs were selected based on breeding cohorts bred in January 2023, where 48 lambs were born with a mean birth weight of 4.11±0.2 kg. The lambs were divided into three groups and randomly assigned to the treatments. The experiment started when the lambs were ten (10) days old. Three dietary treatments, namely creep feed (CF) as control, commercial concentrate A (CA), and concentrate B (CB) with crude protein (CP) at 18.25%, 14.73%, and 13.05%, respectively. The treatments were assumed to be isocaloric feed. The feed given was calculated, and the lambs had free access to water and were permitted to suckle ewes (ad libitum). A GLM procedure was performed to determine the effects of feed and sexes, which are significant for growth traits. The results were that only male lambs fed with CF were significantly higher (p<0.05) on the weaning weight (28.10±1.2 kg) and average daily gain (ADG) (258.08±13.8 g/day) compared with other treatments. However, there is no significant difference (p<0.05) for male and female lambs fed with CA and CB. Therefore, the present finding suggested that the CF could increase the weaning weight and ADG over a short period for male Dorper lambs.